Gamma-ray computed tomography to evaluate changes in the structure of a clayey soil due to agricultural traffic - doi: 10.4025/actasciagron.v33i3.4727 - Pires, Luiz Fernando (2011)
A first generation gamma-ray computed tomography (CT) equipped with a 137Cs source was used to investigate changes in soil structure due to agricultural machinery traffic. Core samples with volume of 55 cm3 were collected at the surface (0-10 cm) of a Brazilian clayey soil. Significant alterations in soil structure occurred after two passages of tractor wheels, with important decreases in soil porosity. CT data allowed a continuous analysis of soil bulk density and also soil porosity distribution for 1.25 and 1.20 mm layers, which cannot be provided by traditional methods commonly used in soil physics.